Induction of Immunogenic Cell Death by Photodynamic Therapy Mediated by Aluminum-Phthalocyanine in Nanoemulsion - Mosar Corrêa Rodrigues; Wellington Tavares de Sousa Júnior; Thayná Mundim; Camilla Lepesqueur Costa Vale; Jaqueline Vaz de Oliveira; Rayane Ganassin; Thyago José Arruda Pacheco; José Athayde Vasconcelos Morais; João Paulo Figueiró Longo; Ricardo Bentes Azevedo; Luis Alexandre Muehlmann (MDPI AG, 2022)
Photodynamic therapy (PDT) has been clinically employed to treat mainly superficial cancer, such as basal cell carcinoma. This approach can eliminate tumors by direct cytotoxicity, tumor ischemia, or by triggering an immune response against tumor cells. Among the immune-related mechanisms of PDT, the induction of immunogenic cell death (ICD) in target cells is to be cited. ICD is an apoptosis modality distinguished by the emission of damage-associated molecular patterns (DAMP). Therefore, this study aimed to analyze the immunogenicity of CT26 and 4T1 treated with PDT mediated by aluminum-phthalocyanine in nanoemulsion (PDT-AlPc-NE). Different PDT-AlPc-NE protocols with varying doses of energy and AlPc concentrations were tested. The death mechanism and the emission of DAMPs-CRT, HSP70, HSP90, HMGB1, and IL-1β-were analyzed in cells treated in vitro with PDT. Then, the immunogenicity of these cells was assessed in an in vivo vaccination-challenge model with BALB/c mice. CT26 and 4T1 cells treated in vitro with PDT mediated by AlPc IC50 and a light dose of 25 J/cm2 exhibited the hallmarks of ICD, i.e., these cells died by apoptosis and exposed DAMPs. Mice injected with these IC50 PDT-treated cells showed, in comparison to the control, increased resistance to the development of tumors in a subsequent challenge with viable cells. Mice injected with 4T1 and CT26 cells treated with higher or lower concentrations of photosensitizer and light doses exhibited a significantly lower resistance to tumor development than those injected with IC50 PDT-treated cells. The results presented in this study suggest that both the photosensitizer concentration and light dose affect the immunogenicity of the PDT-treated cells. This event can affect the therapy outcomes in vivo.